Clinical and pathogenetic variants of peptic ulcer - A. Ya. Kryukova; O. A. Kuramshina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
The authors present some variants of the peptic ulcer course, with pathogenesis of the pathology being taken into account. Attention has been paid to the role of the central nervous system and of the vegetative nervous system as well as to psychosomatic mechanisms of the given pathology development.